Resolution of Breach of Contract Disputes in Franchise Agreements by the Franchisee against the Franchisor in Decision Number 612/Pdt.g/2017/Jkt. Sel - Devi, Devi Fahwi Kurniastuti; Destina Rina Susanti (International Journal of Law and Legal Ethics, 2023)
The purpose of this research is to analyze the resolution of breach of contract disputes in franchise agreementsthrough a case study of Decision No. 612/Pdt.g/2017/Jkt. Considering that contract violations can occur in anylegal agreement, this study aims to examine various measures available to address such issues. The researchutilizes a qualitative approach with primary sources being written laws, namely the Indonesian Civil Code(KUHPerdata), Franchise Agreements, and Licensing Agreements dated April 25 and June 18, 2015, as thevalidity of these agreements is deemed equivalent to law for the involved parties. The focus of the breach ofcontract dispute began when the Defendant failed to pay royalties for the MySalon franchises in Jababeka andGalaxi Bekasi from June 2016 to September 2017, resulting in losses for the Plaintiff. Various steps can betaken to resolve breach of contract disputes, including issuing warnings, conducting negotiations, and resortingto litigation if no agreement is reached. However, due to the Plaintiff's continued evasion and failure to fulfilltheir obligations in good faith, the Plaintiff eventually filed a lawsuit with the South Jakarta District Court onSeptember 12, 2017. The panel of judges ruled that the Defendant had committed breach of contract and wasobligated to compensate the Plaintiff for the incurred material losses